2021
DOI: 10.1111/1755-0998.13378
|View full text |Cite
|
Sign up to set email alerts
|

A library preparation optimized for metagenomics of RNA viruses

Abstract: Our understanding of the viral communities associated to animals has not yet reached the level attained on the bacteriome. This situation is due to, among others, technical challenges in adapting metagenomics using high-throughput sequencing to the study of RNA viromes in animals. Although important developments have been achieved in most steps of viral metagenomics, there is yet a key step that has received little attention: the library preparation. This situation differs from bacteriome studies in which deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 113 publications
(257 reference statements)
0
24
0
Order By: Relevance
“…Duplicate reads had been previously removed with the markdup tool in Samtools (47). Contigs sharing the same best hit were grouped into a viral operational taxonomic unit (vOTU) as previously described (27, 44). Names of vOTUs were generated through combining the best-hit name and the mean percent identity at the amino-acid level of the contigs with the best hit.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Duplicate reads had been previously removed with the markdup tool in Samtools (47). Contigs sharing the same best hit were grouped into a viral operational taxonomic unit (vOTU) as previously described (27, 44). Names of vOTUs were generated through combining the best-hit name and the mean percent identity at the amino-acid level of the contigs with the best hit.…”
Section: Methodsmentioning
confidence: 99%
“…To do so, the vOTUs in the ten libraries of this study were compared to those found in six libraries sequenced in parallel and processed in the same laboratory for another project. These libraries derived from adult females of the mosquito Aedes vexans from Senegal and have been previously described (44). This comparison found 25 vOTUs in common.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations